Hatching Ratio and Larval Development of Aedes aegypti Eggs in Different Growth Media - Rizki, M Ali Azis Hasan; Supardan, Dadan (Universitas Islam Negeri Mataram, 2024)
Aedes aegypti is a mosquito species primarily known as the vector for dengue fever. The Hatching and development larval of Aedes agypti are crtical factors in mosquito control strategies and reducing dengue fever transmission. This study aims to investigate the effects of different water media on the hatching rate and development of Aedes aegypti from egg to adult stage. Three type of water from well water, treated tap water (PDAM) and staw soaked water were used in the experiment. The selection of water sources was based on their distinct physical and chemical properties, representing common environmental condition where Aedes aegypti may breed. Straw soak water was incorporated to simulate organic rich aquatic environments, often characterized by the presence of decomposing plant material. Such conditions are known provide a nutrient rich medium that facilitates mosquito egg hatching and larval development. Eggs were placed in each water type, and observations were carried out at hatching rate and larval development. The result revealed that the straw soaked water had the highest hatching rate 100% and the development time 6 days from egg to adult, well water show a hatching rate 67% with a longer development period of 7 days and no hatching and larval developmet in tap water (PDAM). This study shows that various types of water media affect the hatching success and developmental rates of Aedes aegypti. However, these effects are limited to the specific water types used in the experiment and should not be assumed to apply to all water quality conditions. Future research is recommended to explore other water quality parameters and their potential impact on the mosquito life cycle